Methods and techniquesSuccessful angioplasty of three cases of coronary artery dissections using hydrophilic wires - Ponangi, Udaya Prashant; Menon, Rajeev; Kapadia, Anuj (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Three cases of successful angioplasty of high-grade coronary dissections using hydrophilic wires were reported. Our first case had edge dissection after a stent deployed in the left anterior descending artery, after which we found it impossible to track the second stent over the regular wires, and which was successful when we tried with a stiffer hydrophilic wire. The second had spontaneous coronary artery dissections (SCAD), and the third case was a complicated plaque with multiple stenotic and ectatic segments along with dissection and successful angioplasty carried out using the same wires and without additional hardware. These wires also provided adequate support in tracking the required balloons and stents